Ammonia storage material
Bissulfonylamide salts of specific metals facilitate high-speed ammonia storage and release over a wide temperature range, addressing the inefficiencies of existing ammonia storage materials in achieving rapid and efficient ammonia separation and recovery.
Patent Information
- Application Number
- JP2023153293
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Existing ammonia storage materials have slow ammonia storage and release rates, making it difficult to achieve efficient separation and recovery of ammonia, especially over a wide practical temperature range.
The use of bissulfonylamide salts of alkali metals, alkaline earth metals, and transition metals as ammonia storage materials, which exhibit selective and reversible ammonia storage and release properties over a wide temperature range.
The bissulfonylamide salt-based ammonia storage materials enable high-speed occlusion and release of ammonia, achieving efficient ammonia storage and release characteristics over a practical temperature range from room temperature to 200°C.
Smart Images

Figure 2025045358000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an ammonia storage material capable of absorbing and releasing ammonia. [Background technology]
[0002] In recent years, carbon dioxide emission regulations have led to the need to reduce the use of fossil fuels. Hydrogen, which does not emit carbon dioxide through oxidation or combustion, has been attracting attention as a next-generation fuel to replace fossil fuels, and the use of ammonia (NH3) as a storage and transportation medium for this hydrogen has been considered.
[0003] The Haber-Bosch process, which uses hydrogen and nitrogen, has been used industrially to synthesize and produce ammonia, but it is necessary to separate and recover the synthesized ammonia from the unreacted hydrogen and nitrogen. Conventional ammonia separation and recovery processes include the deep cooling recovery method, which uses the difference in boiling point between ammonia and unreacted gases (hydrogen and nitrogen) to perform liquefaction separation, and the water dissolution separation method, which uses the difference in solubility in water to perform dissolution separation. However, these separation and recovery processes have problems such as energy costs and the inclusion of water vapor.
[0004] In order to solve these problems, the development of ammonia storage materials using materials that exhibit selective ammonia storage properties is underway. For example, the ammonia storage material of Patent Document 1 uses a combination of metal halides such as calcium chloride (CaCl2) and calcium bromide (CaBr2) to selectively store and release synthesized ammonia by controlling pressure and temperature. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4745299 (page 4, figure 8) Summary of the Invention [Problem to be solved by the invention]
[0006] The ammonia storage material of Patent Document 1 can increase the ammonia storage capacity by using a metal halide, but has a problem that the ammonia storage / release rate is slow, which slows down the separation / recovery of ammonia and reduces efficiency. In addition, for practical use, an ammonia storage material is required to have ammonia storage / release characteristics at about 200°C, which is the ammonia discharge temperature in the synthesis / production of ammonia, and at room temperature (27°C), but there has not been an ammonia storage material that can store / release ammonia at high speed over such a wide practical temperature range.
[0007] The present invention has been made in view of these problems, and has an object to provide an ammonia storage material capable of absorbing and releasing ammonia at high speed over a wide practical temperature range. [Means for solving the problem]
[0008] The present inventors have conducted intensive research into the above-mentioned problems and have discovered that by utilizing a bissulfonylamido salt of at least one metal selected from alkali metals, alkaline earth metals and transition metals as a material exhibiting selective ammonia storage properties, an ammonia storage material capable of absorbing and releasing ammonia at high speeds over a wide practical temperature range can be obtained, thereby completing the present invention.
[0009] That is, the ammonia storage material of the present invention contains a salt of at least one metal selected from alkali metals, alkaline earth metals, and transition metals, and a bissulfonylamide anion represented by the following formula (1) (wherein X1 and X2 are halogen or halogenated alkyl groups).
[0010] [ka] [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic diagram showing the crystal structure of a bissulfonylamide salt (Na[TFSA]) contained in an ammonia storage material according to an embodiment. FIG. [Diagram 2] FIG. 2 is a graph showing the ammonia absorption / release behavior at 200° C. of the ammonia absorption material (Na[TFSA]) in Example 1. [Diagram 3] FIG. 1 is a graph showing the ammonia absorption / release behavior of a conventional ammonia absorption material (CaCl2) at 200° C. [Figure 4] 1A is a graph comparing the initial ammonia absorption behavior at 200°C of the ammonia absorption material (Na[TFSA]) in Example 1 and a conventional ammonia absorption material (CaCl2), and FIG. 1B is a graph comparing the initial ammonia release behavior at 200°C. [Diagram 5] 1A is a graph showing the ammonia absorption behavior of the ammonia storage material (Na[TFSA], Ca[TFSA]2, Mg[TFSA]2) in Example 2 at 200°C, and FIG. 1B is a graph showing the ammonia absorption behavior of the ammonia storage material (Na[TFSA], K[TFSA], Ca[TFSA]2, Mg[TFSA]2) in Example 2 at 27°C. [Figure 6] FIG. 1(a) is a graph showing the ammonia absorption / release capacity of the ammonia storage material (TFSA salt) in Example 2 at 200° C. and 27° C., and FIG. 1(b) is a graph showing the ammonia absorption / release capacity of the ammonia storage material (FSA salt) in Example 2 at 50° C. and 27° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described. However, the present invention can be embodied in many different forms, and is not limited to the following embodiments and examples.
[0013] The ammonia storage material according to this embodiment contains a salt of at least one metal selected from alkali metals, alkaline earth metals and transition metals, and a bissulfonylamide anion represented by the above formula (1) (wherein X1 and X2 are halogen or a halogenated alkyl group).
[0014] In the bissulfonylamide anion, when X1 and X2 in the above formula (1) are halogens, X1 and X2 are either fluorine, chlorine, bromine, or iodine. Note that X1 and X2 may both be the same type of halogen or different types of halogens.
[0015] In addition, in the bissulfonylamide anion, when X1 and X2 in the above formula (1) are halogenated alkyl groups, X1 and X2 are any of a fluorinated alkyl group, an alkyl chloride group, an alkyl bromide group, and an alkyl iodide group. Note that X1 and X2 may both be the same type of halogenated alkyl group, or may be different types of halogenated alkyl groups.
[0016] The number of carbon atoms in the halogenated alkyl group is preferably 1 to 4, and more preferably 1 or 2, from the viewpoint of facilitating the formation of a layered crystal structure of the bissulfonylamide salt described below.
[0017] Furthermore, X1 and X2 in the above formula (1) may be a combination of a halogen and a halogenated alkyl group.
[0018] In addition, X1 and X2 in the above formula (1) are preferably fluorine or a fluorinated alkyl group, and examples of such bissulfonylamide anions include a bis(fluorosulfonyl)amide (FSA) anion in which both X1 and X2 are fluorine (X1, X2=F), a bis(trifluoromethylsulfonyl)amide (TFSA) anion in which both X1 and X2 are trifluoromethyl groups (X1, X2=CF3), a (fluorosulfonyl)(trifluoromethylsulfonyl)amide anion in which X1 is a trifluoromethyl group (X1=CF3) and X2 is fluorine (X2=F), and a (trifluoromethylsulfonyl)(pentafluoroethylsulfonyl)amide anion in which X1 is a trifluoromethyl group (X1=CF3) and X2 is pentafluoroethyl (X2=C2F5).
[0019] In addition, the metal may be any of an alkali metal, alkaline earth metal, and transition metal as long as it can form a salt with the bissulfonylamide anion. From the viewpoint of facilitating the formation of a stable salt, however, an alkali metal or an alkaline earth metal is preferable, and the alkali metals sodium or potassium are particularly preferable.
[0020] In addition, the bissulfonylamide salt can absorb and release ammonia in a solid state, and the melting point changes depending on the combination of the metal and the bissulfonylamide anion. The melting points of the bissulfonylamide salt are, for example, 257°C for Na[TFSA], 199°C for K[TFSA], 300°C for Ba[TFSA]2, 130°C for Li[FSA], 106°C for Na[FSA], and 102°C for K[FSA]. In addition, Mg[TFSA]2 and Ca[TFSA]2 have melting points of 200°C or higher, so they can absorb and release ammonia at 200°C. In addition, Ca[FSA]2 has a melting point of 100°C or higher, so they can absorb and release ammonia at 50°C or 27°C.
[0021] That is, the ammonia storage material of the present embodiment can adjust the temperature range in which it can store and release ammonia depending on the bissulfonylamide salt contained therein.
[0022] Here, the crystal structure of the bissulfonylamide salt will be described. For example, Na[TFSA], which is a bissulfonylamide salt, has a layered crystal structure as shown in Figure 1. It has been confirmed that the layered crystal structure of the bissulfonylamide salt expands and contracts, particularly in the c-axis direction (see Figure 1), upon absorption and release of ammonia, and it is presumed that ammonia is absorbed between the layers of the layered crystal structure.
[0023] In addition, it has been confirmed that NH4[TFSA] is generated by the absorption of ammonia in bissulfonylamide salts, for example, Ca[TFSA]2 and Mg[TFSA]2. Ammonia is mainly adsorbed on the surface of the cationic site between the layers of the layered crystal structure, and NH4 is absorbed into the bissulfonylamide anion of TFSA, etc. + It is presumed that bulk adsorption (dissolution) occurs due to the coordination of
[0024] In this way, the bissulfonylamide salt is capable of selectively and reversibly chemically adsorbing ammonia between the layers of the layered crystal structure, enabling it to absorb and release ammonia at high speed.
[0025] The ammonia storage material of the present embodiment is not limited to being composed only of a bissulfonylamide salt, and may contain other materials such as a binder as long as it contains a bissulfonylamide salt as a main component. That is, in the present embodiment, the composition of the ammonia storage material is such that the bissulfonylamide salt accounts for 45 mass% or more.
[0026] The ammonia occlusion material of the present embodiment may be in the form of a powder or granules, or may be formed into pellets, tablets, or the like.
[0027] As described above, the ammonia storage material of the present embodiment contains a salt of at least one metal selected from alkali metals, alkaline earth metals, and transition metals and a bissulfonylamide anion, and can store and release ammonia at high speed in a wide practical temperature range. The practical temperature range is a temperature range from room temperature (27°C) to about 200°C, which is the ammonia discharge temperature during the synthesis and production of ammonia, and is about 0 to 500°C. EXAMPLES
[0028] Here, an ammonia storage material according to Example 1 of the above embodiment was actually produced, and its effects were confirmed.
[0029] The ammonia storage material in this example is a column packed with granular Na[TFSA] (S0989 manufactured by Tokyo Chemical Industry Co., Ltd.), and ammonia is stored and released by pressure operation (PSA) of 0.1 to 0.5 MPa. Figure 2 shows the ammonia storage and release behavior of Na[TFSA] at 200°C.
[0030] As shown in FIG. 2, in the ammonia storage material (Na[TFSA]) of this example, the amount of ammonia absorbed increased with increasing ammonia pressure at 200°C, and the amount of ammonia absorbed decreased with decreasing ammonia pressure. This confirmed that the ammonia storage material can repeatedly absorb and release ammonia by controlling the pressure.
[0031] In addition, at 200°C, the ammonia storage capacity of the ammonia storage material (Na[TFSA]) of this example decreased to 0 mmol g -1It was confirmed that the ratio of the ammonia release capacity to the ammonia storage capacity was 95% or more, showing reversible ammonia storage / release characteristics. Note that, since the ratio of the ammonia release capacity to the ammonia storage capacity of a conventional ammonia storage material (CaCl2) made of a metal halide at 200°C is about 50% (see FIG. 3), the ammonia storage material of this example (Na[TFSA]) has excellent reversible ammonia storage / release characteristics.
[0032] FIG. 4 shows the results of comparing the initial ammonia absorption behavior and initial ammonia release behavior at 200° C. of the ammonia absorption material (Na[TFSA]) of this embodiment with a conventional ammonia absorption material (CaCl2).
[0033] As shown in FIG. 4(a), the ammonia storage material (Na[TFSA]) of this example absorbed approximately 2 mmol g of ammonia in approximately 1 minute and 30 seconds from the start of ammonia absorption at 200°C. -1 This corresponds to the final ammonia storage capacity (approximately 3 mmol g -1 , see Figure 2). In contrast, the amount of ammonia absorbed by the conventional ammonia absorber (CaCl2) was approximately 2 mmol g -1 This is due to the final ammonia storage capacity (approximately 16 mmol g -1 This is approximately 13% of the total (see Figure 3).
[0034] In addition, as shown in FIG. 4(b), the ammonia storage material (Na[TFSA]) of this example reached ammonia storage capacity of 0 mmol g in about 14 minutes after the start of ammonia release at 200°C. -1 The amount of ammonia absorbed by the conventional ammonia absorber (CaCl2) did not change for about 14 minutes after the ammonia release started, and no ammonia was released.
[0035] From these findings, it was confirmed that the ammonia storage material (Na[TFSA]) of this example is capable of absorbing and releasing ammonia at high speed at 200°C.
[0036] Moreover, as shown in FIG. 4(b), the ammonia storage material (Na[TFSA]) of this embodiment releases almost the entire amount (95% or more) of the ammonia storage amount in about 14 minutes from the start of ammonia release at 200°C. In contrast, the conventional ammonia storage material (CaCl2) releases only half (50%) of the ammonia storage amount in about 40 minutes from the start of ammonia release. In other words, it was confirmed that the ammonia storage material (Na[TFSA]) of this embodiment is capable of absorbing and releasing ammonia at high speed and high efficiency at 200°C. EXAMPLES
[0037] Here, an ammonia storage material according to Example 2 of the above embodiment was actually produced, and its effects were confirmed.
[0038] The ammonia storage material in this embodiment is a column packed with granular Na[TFSA] (S0989 manufactured by Tokyo Chemical Industry Co., Ltd.), K[TFSA] (B2543 manufactured by Tokyo Chemical Industry Co., Ltd.), Ca[TFSA]2 (C3263 manufactured by Tokyo Chemical Industry Co., Ltd.), and Mg[TFSA]2 (M2861 manufactured by Tokyo Chemical Industry Co., Ltd.), and the results of ammonia storage at 200 ° C and 27 ° C by pressure operation (PSA) of 0.1 to 0.5 MPa are shown in Figure 5. Note that since K[TFSA] has a melting point of 199 ° C, the ammonia storage behavior at 200 ° C is shown for three ammonia storage materials (Na[TFSA], Ca[TFSA]2, Mg[TFSA]2) excluding K[TFSA] (see Figure 5 (a)).
[0039] As shown in Fig. 5(a), at 200 °C, Na[TFSA] absorbed approximately 2.9 mmol g ammonia in 10 min from the start of ammonia absorption. -1 This corresponds to the final ammonia storage capacity (approximately 3 mmol g-1 2 and 6(a)). At 200°C, the amount of ammonia absorbed by Ca[TFSA]2 was approximately 4.1 mmol g -1 This corresponds to the final ammonia storage capacity (approximately 5.2 mmol g -1 , see Fig. 6(a). At 200 °C, Mg[TFSA]2 absorbed about 5.5 mmol g -1 This corresponds to the final ammonia storage capacity (approximately 8.3 mmol g -1 , see Figure 6(a)).
[0040] As shown in Fig. 5(b), at 27 °C, Na[TFSA] absorbed approximately 21.5 mmol g ammonia in 10 min from the start of ammonia absorption. -1 This corresponds to the final ammonia storage capacity (approximately 23.3 mmol g -1 , see Fig. 6(a). At 27°C, K[TFSA] was approximately 16.0 mmol g -1 This corresponds to the final ammonia storage capacity of approximately 17.9 mmol g -1 , see Figure 6(a). At 27°C, the amount of ammonia absorbed by Ca[TFSA]2 was approximately 18.2 mmol g -1 This corresponds to the final ammonia storage capacity of approximately 21.6 mmol g -1 , see Fig. 6(a). At 27°C, Mg[TFSA]2 absorbed ammonia at a rate of approximately 8 mmol g -1 This corresponds to the final ammonia storage capacity of approximately 11.2 mmol g -1 , see Figure 6(a)).
[0041] Thus, it was confirmed that the ammonia storage material in this example has different ammonia storage and release characteristics depending on the metal (cation species) even if it is the same TFSA salt at 200° C. and 27° C. In addition, it was confirmed that at 200° C. and 27° C., all ammonia storage materials can store and release ammonia at a higher speed than ammonia storage materials made of conventional metal halides, and in particular, Na[TFSA] can store and release ammonia at a higher speed at 200° C., and Na[TFSA] and K[TFSA] can store and release ammonia at a higher speed at 27° C.
[0042] In addition, the ammonia storage material made of conventional zeolite (Na·Y zeolite) can absorb and release ammonia at the same speed as the ammonia storage material of this embodiment at 200°C, but at room temperature (27°C), it can absorb ammonia, but it has the problem that it releases ammonia slowly and has a small release capacity (poor reversibility). This is presumably because, in the case of zeolite, ammonia is absorbed in the countless pores that are the characteristic structure of zeolite, making it difficult to release ammonia at room temperature. In contrast, the ammonia storage material of this embodiment is capable of absorbing and releasing ammonia at high speed even at low temperatures such as room temperature, because ammonia is absorbed between the layers of the layered crystal structure of the bissulfonylamide salt.
[0043] Furthermore, it was confirmed that among the ammonia storage materials of this example, K[TFSA] in particular is capable of absorbing and releasing ammonia at high speed at 27°C, and exhibits reversible ammonia absorption and release characteristics, with the ratio of the release capacity to the ammonia storage capacity being approximately 100%.
[0044] As shown in Figure 6(b), it was also confirmed that the ammonia absorption and release characteristics of FSA salts (Li[FSA], Na[FSA], K[FSA], Ca[FSA]2) differ depending on the metal (cation type). It was also confirmed that FSA salts have a lower melting point overall than TFSA salts, but have a larger ammonia absorption capacity.
[0045] As described above, these embodiments and examples make it possible to provide an ammonia storage material capable of absorbing and releasing ammonia at high speed over a wide practical temperature range.
[0046] Incidentally, the discharge temperature of ammonia during the synthesis and production of ammonia is approximately 200°C. However, since the temperature of ammonia is lower on the downstream side (outlet side) of the absorption column than on the upstream side (inlet side), taking into consideration the difference in the temperature of ammonia at the inlet and outlet of the absorption column, the composition of the ammonia absorption material may be changed so that, for example, Na[TFSA], which has excellent ammonia absorption and release properties at 200°C, is mainly placed on the upstream side of the absorption column, and bissulfonylamide salts (TFSA salts, FSA salts) that correspond to the reduced ammonia temperature are mainly placed on the downstream side of the absorption column.
[0047] In the above embodiment, the storage and release of ammonia is performed by pressure operation (PSA). However, the present invention is not limited to this, and the storage and release of ammonia may be performed by temperature operation (TSA) or pressure and temperature operation (PTSA). [Industrial Applicability]
[0048] The present invention has industrial applicability as an ammonia storage material capable of absorbing and releasing ammonia at high speed over a wide practical temperature range. In addition, the present invention is capable of adjusting the absorption and release characteristics such as the ammonia absorption and release speed and reversibility by combining the metal and bissulfonylamide anion that constitute the bissulfonylamide salt, which is the main component of the ammonia storage material, and therefore enables highly efficient separation and recovery of ammonia over a wide practical temperature range, and has a wide range of applications.
Claims
1. At least one metal selected from alkali metals, alkaline earth metals and transition metals, and a bissulfonylamide anion represented by the following formula (1) (wherein X 1 , X 2 is a halogen or a halogenated alkyl group.
2. X in the formula (1) 1 , X 2 2. The ammonia storage material according to claim 1, wherein: is fluorine or a fluoroalkyl group.
3. 3. The ammonia storage material according to claim 2, wherein the bissulfonylamide anion is a bis(trifluoromethylsulfonyl)amide anion.
4. 3. The ammonia storage material according to claim 2, wherein the bissulfonylamide anion is a bis(fluorosulfonyl)amide anion.
5. 5. The ammonia storage material according to claim 1, wherein the metal is sodium.
6. 5. The ammonia storage material according to claim 1, wherein the metal is potassium. 【Chemistry 1】
Citation Information
Patent Citations
Ammonia adsorbent / desorbent, separation method, and storage method using a specific combination of metal halides
JP4745299B2